Food Cover Using Solar Technology (So.Tech Food) / Fan Hafiqah Rodiah Abdul Jabar - Abdul Jabar, Fan Hafiqah Rodiah (2020)
People want a technology that friendly user and multi-function of food cover for busy person to make them easy to keep the food keep warm and can eat without heating. Therefore, Daisy Solar Co. introduce an invention of food cover which is So. Tech Food has come out with an idea in developing and upgrading design of existence food cover to solve the problem for all consumer. This blueprint will be discussing on our new technology development called “So. Tech Food”. The So. Tech Food is built with 5 persons. It is a partnership company that manufactures was located at Johor Bahru. Besides, under marketing, we will hire two staff to help in promoting strategies regarding our products. While under the operation, we will hire three staffs to develop the product. The concept of our company’s product is “Convenient for All” since The So. Tech Food is user friendly. Peoples who like to keep food warmth for longer after cooked and person who only cooked once in a day are really suitable to use a food cover from our great collection. Thus, from the point of view on who is going to purchase our product are to all busy persons and food tenders who concerned about their quality of food after cooked. Therefore, we can guarantee that our product will be a successful product in Malaysia’s market. There are a few competitors in the market that have been in this industry earlier than Daisy Solar Co. for example Sharp and Panasonic (electronic shops). The So. Tech Food can compete with the product from those companies because it has new features and will be well-known in Malaysia’s market.